Estuarine and coastal modeling : proceedings of the sixth international conference November 3-5, 1999, New Orleans, Louisiana - International Conference on Estuarine and coastal modeling (6th 2000 : New Orleans, LA); Spaulding, Malcolm L. (Reston, VA : American Society of Civil Engineers, 2000)
47